Effectiveness of subcutaneous implantable cardioverter-defibrillator testing in patients with hypertrophic cardiomyopathy. (15th March 2017) - Maurizi, Niccoló; Tanini, Ilaria; Olivotto, Iacopo; Amendola, Ernesto; Limongelli, Giuseppe; Losi, Maria Angela; Allocca, Giuseppe; Perego, Giovanni Battista; Pieragnoli, Paolo; Ricciardi, Giuseppe; De Filippo, Paolo; Ferrari, Paola; et al.
Abstract: Background: Subcutaneous ICD (S-ICD) is a promising option for Hypertrophic Cardiomyopathy (HCM) patients at risk of Sudden Cardiac Death (SCD). However, its effectiveness in terminating ventricular arrhythmias in HCM is yet unresolved. Methods: Consecutive HCM patients referred for S-ICD implantation were prospectively enrolled. Patients underwent one or two attempts of VF induction by the programmer. Successful conversion was defined as any 65 J shock that terminated VF (not requiring rescue shocks). Clinical and instrumental parameters were analyzed to study predictors of conversion failure. Results: Fifty HCM patients (34 males, 40 ± 16 years) with a mean BMI of 25.2 ± 4.4 kg/m2 were evaluated. Mean ESC SCD risk of was 6.5 ± 3.9% and maximal LV wall thickness (LVMWT) was 26 ± 6 mm. In 2/50 patients no arrhythmias were inducible, while in 7 (14%) only sustained ventricular tachycardia was induced and cardioverted. In the remaining 41 (82%) patients, 73 VF episodes were induced (1 episode in 14 and > 1 in 27 patients). Of these, 4 (6%) spontaneously converted. In 68/69 (98%) the S-ICD successfully cardioverted, but failed in 1 (2%) patient, who needed rescue defibrillation. This patient was severely obese (BMI 36) and LVMWT of 25 mm. VF was re-induced and successfully converted by the 80 J reversed polarity S-ICD. Conclusions: Acute DT at 65 J at the implant showed the effectiveness of S-ICD in the recognition and termination of VT/VF in all HCM patients except one. Extreme LVH did not affect the performance of the device, whereas severe obesity was likely responsible for the single 65 J failure.